Some results related to constrained non-differentiable (non- smooth) pseudolinear minimization problems - DWIVEDI, RAJNISH KUMAR; PATHAK, ANIL (The journal of contemporary issues in business and government, 2021)
This paper deals with the minimization of a class of non-differentiable (non- smooth) pseudolinear functions over a closed and convex set subject to linear inequality constraints. The properties of locally Lipschitz pseudolinear functions are used to establish several Lagrange multiplier characterizations of the solution set of the minimization problem. We derive certain conditions, under which an efficient solution becomes a properly efficient solution of a constrained non-differentiable minimization problem.